Luminescent properties of yttrium diphenylphosphinate activated by europium - Francisco, Cristina S.; Stucchi, Elizabeth B.; de Abreu, Edson M. (Elsevier B.V., 2006)
The synthesis and spectroscopic characterization of yttrium diphenylphosphinates doped with europium are reported. The purity of all samples was confirmed by carbon and hydrogen micro analysis, thermal analysis, IR vibrational spectroscopy, and X-ray diffraction. Luminescence spectra indicated the presence of two or more symmetry centers. The dynamic luminescence measurements suggested that one symmetry site presented an inversion center, while the others had lower symmetry. The average quantum yield of Eu3+ emission in the yttrium, matrices was 60%. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: yttrium diphenylphosphinate; luminescence spectroscopy; europium; quantum yield